THE ROLE OF MOLECULAR GENETIC MARKERS IN THE CLINICAL COURSE OF CERVICAL INTRAEPITHELIAL NEOPLASIA - Nazhmutdinova , Dilbar; Kamilova , Iroda; Shukurova , Umida (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
When studying the clinical course of cervical intraepithelial neoplasia in 226 women with molecular genetic analysis, it was revealed that the correlation of alleles and genotypes of genes of oncosuppressor proteins, enzymes of estrogen metabolism and matrix metalloproteinases, confirmed by indicators of relative risk, were the basis for establishing the severity of the clinical course and the risk of developing this multifactorial pathology, by studying anamnestic, somatic data, complaints and the presence of urogenital infections in women with neoplasia of the cervical epithelium.